Testing Integrative Models to Improve School Safety: Positive Behavior Interventions and Supports and the Olweus Bullying Prevention Program, South Carolina, 2015-2018 - Limber, Sue ([Verlag nicht ermittelbar], 2020)
Many schools have implemented programs to address bullying, such as the Olweus Bullying Prevention Program (OBPP), or broader school behavioral issues, such as School-wide Positive Behavioral Interventions and Supports (SWPBIS), but there have been calls to integrate school interventions in order to address the limits of each "stand alone" program. The purpose of this project was to develop an intervention combining OBPP and SWPBIS strategies into one integrated program, evaluate its effectiveness using a randomized controlled trial (RCT), analyze the program's cost effectiveness, and examine the use of school-based mental health services in elementary, middle, and high school settings. Implications for policy and strategy are also discussed. School-level data were presented including disciplinary incidents, student and teacher attendance, program costs, and the presence of mental health services. Students and teachers within intervention and control conditions were surveyed about their perceptions of bullying, school safety, and school climate. Teachers in intervention schools were asked about program satisfaction, self-efficacy, and fidelity. Students were asked numerous questions pertaining to physical and mental health, bullying perpetration and victimization, and substance abuse. Teachers and students were asked their grade, gender, and race.